Contesting Indochina : French Remembrance between Decolonization and Cold War - Edwards, M. Kathryn, 1979- (Book collections on Project MUSE., 2016)
"How does a nation come to terms with losing a war--especially an overseas war the purpose of which is fervently contested? In the ensuing years, how does such a nation construct and reconstruct its identity and values? For the French in Indochina, the stunning defeat at Dien Bien Phu ushered in the violent process of decolonization and a fraught reckoning with a colonial past. Contesting Indochina is the first in-depth study of the competing and intertwined narratives of the Indochina War. It analyzes the layers of French remembrance, focusing on state-sponsored commemoration, veterans' associations, special-interest groups, intellectuals, films, and heated public disputes. These narratives make up the ideological battleground for contesting the legacies of colonialism, decolonization, the Cold War, and France's changing global status"--Provided by publisher.